The human circulatory system learning during the covid-19 pandemic: Video media equipped with crossword puzzle - Rambu Feny Radandima; Vidriana Oktoviana Bano; Anita Tamu Ina (JPBIO (Jurnal Pendidikan Biologi), 2022)
The provision of variations in the use of media equipped with methods in learning is carried out in order to attract students in learning during the Covid-19 pandemic which aims to find out the influence of the use of video learning media equipped with crossword puzzle type Student Worksheets (LKPD), on learning outcomes during the Covid-19 pandemic; This type of research is experimental research, using a mixed methods approach with the concurrent triangulation design method. The results showed that: (1) there was a positive influence on the use of video learning media equipped with crossword puzzle type Student Worksheets on learning outcomes, shown from the results of the hypothesis test, namely 0.000 or Sig values. < 0.05; (2) there are differences in student learning outcomes between the use of power point learning media (PPT) and video learning media equipped with crossword puzzle type LKPD, shown by the average posttest of the control class 56.56 and the posttest of the experimental class 82.76. It can be concluded that the use of video media equipped with crossword puzzle type LKPD has a positive influence on learning outcomes on human circulatory system material during the Covid-19 pandemic.